If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + 2(3X + 2) = 28 Reorder the terms: 3X + 2(2 + 3X) = 28 3X + (2 * 2 + 3X * 2) = 28 3X + (4 + 6X) = 28 Reorder the terms: 4 + 3X + 6X = 28 Combine like terms: 3X + 6X = 9X 4 + 9X = 28 Solving 4 + 9X = 28 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 9X = 28 + -4 Combine like terms: 4 + -4 = 0 0 + 9X = 28 + -4 9X = 28 + -4 Combine like terms: 28 + -4 = 24 9X = 24 Divide each side by '9'. X = 2.666666667 Simplifying X = 2.666666667
| 954(3)=p | | 9a-5=2a | | 8x^3-13=-77 | | .4x-2.3=-1.1 | | 5x-8+3x=-10 | | 16t^2+16t-480=0 | | 6(t-2)=2(9-2f) | | 2s-12+12s=4s-12 | | 0.5(8x-4)=10x-9 | | -3x-152+40x=20 | | 12=.99x+20.76 | | 3(x+17.50)=136.50 | | 0=(x^3)-(x^2)-20 | | X+2=16-28 | | 8(x-1)-2(3x-1)=x-1 | | -5t+5=-5 | | 2-2(5y+7)=2(-6-2)+1 | | 5(g+12)=145 | | 0=x^3-7x^2-9x+63 | | -3c+2=7 | | 20+2x=4x-68 | | 0.1x+x=93 | | 8x-7=3z-7z+5 | | 8x+4-36x+9=3 | | 4i=2 | | 4x^2-25y^2+8x+50y-121=0 | | 4x^2-43+63=0 | | a+c=1 | | 0=x^2+3x+9 | | 8*(x+2)=4*(x+5) | | 9x-6=11-2(X-8) | | -(1+8x)=35+4x |